Leaf Phosphorus Fractions Are Coordinated with Leaf Functional Traits in Four Juvenile Tree Species from the Chinese Subtropics - Lei Wang; Jinhong Guan; Zongpei Li; Zhijie Chen; Zaipeng Yu; Zhichao Xia (Plants)
Phosphorus (P) is essential for cellular processes, and P fractions within leaf tissues reflect distinct biochemical functions. However, the relationship among foliar P allocation, leaf functional traits, and soil properties in subtropical China remains poorly understood. Here, we investigated four tree species to examine the relationships among foliar P fractions (orthophosphate P, metabolic P, nucleic acid P, lipid P, and residual P), key leaf functional traits (LMA, Amass, and leaf [N], and P concentrations), and soil properties. A negative correlation between the relative allocation of metabolic P (rPM) and nucleic acid P (rPN) suggested a trade-off between metabolic activity and growth. LMA was positively correlated with rPM and residual P (rPR) but negatively associated with rPN and lipid P (rPL). Similarly, leaf [N] correlated positively with rPN and negatively with rPR. Structural equation modeling (SEM) revealed that foliar P allocation was primarily driven by leaf functional traits independent of soil properties. These findings underscore the critical role of leaf functional traits in shaping P allocation patterns and highlight the adaptive strategies of tree species to cope with P-deficient environments in subtropical ecosystems.